Spatial Location in Brief, Free-Viewing Face Encoding Modulates Contextual Face Recognition. (August 2013) - Felisberti, Fatima M.; McDermott, Mark R.
The effect of the spatial location of faces in the visual field during brief, free-viewing encoding in subsequent face recognition is not known. This study addressed this question by tagging three groups of faces with cheating, cooperating or neutral behaviours and presenting them for encoding in two visual hemifields (upper vs. lower or left vs. right). Participants then had to indicate if a centrally presented face had been seen before or not. Head and eye movements were free in all phases. Findings showed that the overall recognition of cooperators was significantly better than cheaters, and it was better for faces encoded in the upper hemifield than in the lower hemifield, both in terms of a higher d' and faster reaction time (RT). The d' for any given behaviour in the left and right hemifields was similar. The RT in the left hemifield did not vary with tagged behaviour, whereas the RT in the right hemifield was longer for cheaters than for cooperators. The results showed that memory biases in contextual face recognition were modulated by the spatial location of briefly encoded faces and are discussed in terms of scanning reading habits, top-left bias in lighting preference and peripersonal space.